Designing a survey to monitor multi-scale impacts of agri-environment schemes on mobile taxa. (15th July 2021) - Staley, J.T.; Redhead, J.W.; O'Connor, R.S.; Jarvis, S.G.; Siriwardena, G.M.; Henderson, I.G.; Botham, M.S.; Carvell, C.; Smart, S.M.; Phillips, S.; Jones, N.; McCracken, M.E.; et al.
Abstract: Agri-environment schemes (AES) are key mechanisms to deliver conservation policy, and include management to provide resources for target taxa. Mobile species may move to areas where resources are increased, without this necessarily having an effect across the wider countryside or on populations over time. Most assessments of AES efficacy have been at small spatial scales, over short timescales, and shown varying results. We developed a survey design based on orthogonal gradients of AES management at local and landscape scales, which will enable the response of several taxa to be monitored. An evidence review of management effects on butterflies, birds and pollinating insects provided data to score AES options. Predicted gradients were calculated using AES uptake, weighted by the evidence scores. Predicted AES gradients for each taxon correlated strongly, and with the average gradient across taxa, supporting the co-location of surveys across different taxa. Nine 1 × 1 km survey squares were selected in each of four regional blocks with broadly homogenous background habitat characteristics. Squares in each block covered orthogonal contrasts across the range of AES gradients at local and landscape scales. This allows the effects of AES on species at each scale, and the interaction between scales, to be tested. AES options and broad habitats were mapped in field surveys, to verify predicted gradients which were based on AES option uptake data. The verified AES gradient had a strong positive relationship with the predicted gradient. AES gradients were broadly independent of background habitat within each block, likely allowing AES effects to be distinguished from potential effects of other habitat variables. Surveys of several mobile taxa are ongoing. This design will allow mobile taxa responses to AES to be tested in the surrounding countryside, as well as on land under AES management, and potentially in terms of population change over time. The design developed here provides a novel, pseudo-experimental approach for assessing the response of mobile species to gradients of management at two spatial scales. A similar design process could be applied in other regions that require a standardized approach to monitoring the impacts of management interventions on target taxa at landscape scales, if equivalent spatial data are available. Highlights: Agri-environment schemes (AES) are key conservation policies in many countries. A novel design was developed to monitor mobile taxa responses to AES at two scales. Survey sites covered orthogonal contrasts across local and landscape AES gradients. These AES gradients are independent of other background habitat variables. This novel design monitors habitat management effects at varying spatial scales. .